kesalahan dalam menyelesaikan soal bentuk aljabar ditinjau dari gaya belajar siswa - Muh. Muhlas; Nurul Hikmah; Junaidi (STKIP Subang, 2025)
This study aims to describe the types and causes of student errors in solving algebraic problems in terms of learning styles. Analysis of student errors using Newman's error procedure. This type of research is descriptive qualitative research. The initial subjects in this study were students of class VIIA and VIIB SMPN 2 Pringgarata in the 2025/2026 academic year and the final subjects were 10 students selected based on their learning style type by looking at their dominant learning style. The instruments used were (i) Learning style questionnaire, used to determine the type of student learning style, (ii) Written test, used to find the type of student errors using Newman's error procedure, (iii) Interview, used to find the causes of student errors in solving problems. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of this study were 10 selected subjects, namely 5 students with visual learning style types, 2 students with auditory learning style types and 3 students with kinesthetic learning style types. Students with visual learning styles tend to make mistakes at the process skills and conclusion writing stages, the cause of these mistakes is because they do not know the right steps to solve the problem, are in a hurry so they forget to write the conclusion. Students with auditory learning styles tend to make mistakes at the transformation, process skills and conclusion writing stages, the cause of these mistakes is because they do not know how to make mathematical equations and models, do not know what formulas to use and do not know the steps to solve the problem. Students with kinesthetic learning styles tend to make mistakes at the reading, understanding, process skills and conclusion writing stages, the cause of these mistakes is because students are unable to understand the meaning of the problem correctly, are unable to find the steps to solve the problem correctly, rewrite previous mistakes at the conclusion writing stage and even do not know what to write at the conclusion writing stage.